OP0130 IN VITRO CHARACTERIZATION OF INFLAMMATORY ARTHRITIS ASSOCIATED WITH IMMUNE CHECK POINT INHIBITION. (2nd June 2020) - Sørensen, A. S.; Nørgaard Andersen, M.; Juul-Madsen, K.; Skejø, C.; Schmidt, H.; Vorup-Jensen, T.; Kragstrup, T. W.
Abstract : Background: During cancer treatment with immune checkpoint inhibitors (ICI) such as the anti-PD-1 antibody pembrolizumab, 2-4% of patients develop inflammatory arthritis as an immune related adverse event and half of patients with pre-existing inflammatory arthritis have disease flares. This type of adverse events shows striking similarities with traditional immune mediated inflammatory arthritis. However, the underlying immunological mechanisms of inflammatory arthritis associated with ICI are not fully understood. Objectives: We aimed to develop an in vitro model of inflammatory arthritis associated with ICI, and to use this model to investigate monocyte differentiation and activation following treatment with pembrolizumab. Methods: First, synovial fluid mononuclear cells (SFMCs) and peripheral blood mononuclear cells (PBMCs) from patients with immune mediated inflammatory arthritis (rheumatoid arthritis and peripheral spondyloarthritis, n=22) and PBMCs from healthy controls were incubated with pembrolizumab and assessed for monocyte chemoattractant protein 1 (MCP-1) secretion by ELISA. Then, cytokine production in SFMCs was studied in more detail by the multiplex V-PLEX proinflammatory panel and by intracellular flow cytometry. Finally, pembrolizumab treated SFMCs were incubated with the different disease modifying anti-rheumatic drugs adalimumab, tocilizumab, tofacitinib, and baricitinib. Results: Pembrolizumab significantly increased MCP-1 production in the SFMCcultures (P=0.0031). In contrast, pembrolizumab did not change MCP-1 production by PBMCs from neither patients nor healthy controls (P=0.77 and P=0.43). Pembrolizumab also increased the production of TNFα (P=0.049), IFNγ (P=0.047), and IL-12p70 (P=0.031), but did not change the production of IL-6 (P=0.98). Among SFMCs treated with pembrolizumab there was an increased frequency of intermediate monocytes (P=0.044). Interestingly, pembrolizumab also increased the MCP-1 production within the intermediate monocytes only (P=0.028). In contrast, among SFMCs treated with LPS, only the classical monocyte subset was increased (P=0.0045) and MCP-1 production increased in both intermediate and classical monocyte subsets. Lastly, the TNFα inhibitor adalimumab and the Janus kinase inhibitors baricitinib and tofacitinib attenuated the pembrolizumab-induced MCP-1 production (P=0.0004, P=0.033, and P=0.025, respectively) while this was not seen with the IL-6 inhibitor tocilizumab (P=0.75). Conclusion: We have developed a very simple in vitro model of inflammatory arthritis associated with ICI. Using this model, we found that pembrolizumab specifically activated intermediate monocytes and induced TNFα, IFNγ, and IL-12p70 production, whereas IL-6 was unchanged. These findings were supported by effectful reduction of MCP-1 secretion with TNFα inhibition but not with IL-6 inhibition. This model could potentially be used to further study the effects of ICIs and the underlying immunological mechanisms of inflammatory arthritis associated with ICI. References: None. Disclosure of Interests: Anne Sofie Sørensen: None declared, Morten Nørgaard Andersen: None declared, Kristian Juul-Madsen: None declared, Cæcilie Skejø: None declared, Henrik Schmidt: None declared, Thomas Vorup-Jensen: None declared, Tue Wenzel Kragstrup Shareholder of: iBio Tech ApS, Consultant of: Bristol-Myers Squibb, Speakers bureau: TWK has engaged in educational activities talking about immunology in rheumatic diseases receiving speaking fees from Pfizer, Bristol-Myers Squibb, Eli Lilly, Novartis, and UCB.